Tamiang Kolem a New Innovative Karawitan Composition | Tamiang Kolem Sebuah Komposisi Karawitan Inovatif - Dewa Gde Aris Wahyudiatmika (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Tamiang Kolem composition is a musical composition referring to the representation of one object that describes a form of reringgitan and jejaitan that leads to the elements of yadnya. In music, Tamiang Kolem is likened to a word that describes the dynamic and diatonic movement of musical sentences. Tamiang Kolem was created based on the continuity of the Gamelan character Semar Pagulingan as a medium of expression. Tamiang Kolem was created with the aim of increasing the knowledge and expertise of stylists to build the ability to create innovative compositions based on simple thoughts on the relevance of the characteristics of ideas to the characteristics of Semar Pagulingan. In realizing the composition of Tamiang Kolem, the stylist uses the Rogger Session creation method which consists of three stages, namely, the inspiration stage, the conception stage and the execution stage. The composition of Tamiang Kolem is presented as an innovative composition with a structural part consisting of three parts on the object and shape on the tamiang and kolem. Innovative composition is a compositional work that tends to explore ideas or ideas which are basically still visible from traditional material. Keywords : Tamiang Kolem, Composition, Semar Pagulingan Gamelan, Innovative